Synthesis and antitussive evaluation of verticinone-cholic acid salt, a novel and potential cough therapeutic agent - Xu Fang-zhou; Chen Chang; Zhang Yong-hui; Ruan Han-li; Pi Hui-fang; Zhang Pong; Wu Ji-zhou (Acta Pharmacologica Sinica; Vol 28, No 10 (October 2007): Acta Pharmacologica Sinica, 2016)
Aim: To seek a novel and potent antitussive drug based on Shedan—Chuanbei powder, a complex of traditional Chinese medicine preparation for cough therapy. Methods: Verticinone—cholic acid (Ver—CA) salt, a novel, salifying derivative of verticinone and cholic acid, both of which are the major bioactive components in Shedan—Chuanbei powder, was synthesized. We then evaluated the antitussive activity and the acute toxicity of the salt. Results: The new compound, with good solubility in water, has much more potent antitussive activity in comparison with the same dose of single verticinone and single cholic acid. The administration 3 mg/kg of Ver—CA could result in over 50% reduction of a citric acid-induced cough. Pretreatment with naloxone (0.8 mg/kg, ip) can only partially antagonize its anti-tussive effect. On the other hand, glybenclamide (3 mg/kg, ip), an ATP-sensitive K+ channel blocker, can also significantly reduce the antitussive effect of Ver—CA. A further acute toxicity study showed that the LD50 values of Ver—CA were 3 times that of verticinone. Conclusion: Based on the studies of pharmacology and acute toxicity, the salt has a synergic and attenuated toxicity compared with single verticinone and cholic acid. Moreover, the present study also suggests that Ver—CA, a potential novel antitussive agent, may exert its antitussive effect via both the peripheral (modulated by ATP-sensitive K+ channels) and central mechanisms (modulated by the opioid receptor).